Technical report: maximum sustainable yield of squid population by using Gordon-Schaefer model a case study in Malaysia / Hazwani Ahmad Dahari, Jamilah Md Zain and Noor Shahirah Jamaluddin - Ahmad Dahari, Hazwani; Md Zain, Jamilah; Jamaluddin, Noor Shahirah (2016)
Improving the economic performance of fisheries is becoming increasingly important in fisheries management, and in some cases, maximum sustainable yield (MSY) is set as key management target. This research study is conducted on harvesting of squid population in Malaysia. Squid is one of the species threatened with extinction due to overfishing. The modem technology has increased the fishing capacity year by year. Hence, it is very vital to estimate the maximum sustainable yields, so that the squid can continuously be harvested and at the same time this species will not extinct. In this paper, we will identify maximum sustainable yield (MSY) of squid population using Gordon-Schaefer model approach. Gordon-Schaefer Model is a bio-economic model to compute the maximum sustainable yield (MSY). Besides that, this paper also attempts to control the quota of squid that can be caught at a time. Gordon-Schaefer Model incorporates the logistic model to capture the population dynamics. Therefore, the sustainable levels of fishing effort and biomass growth can be proposed to related body that over sees fishing operation. From our study, total of squid landings are not overfishing so the fishermen can still increase their catch for the year 2014 onwards. The total of effort catch has exceeds the value of Maximum Sustainable Yield and this means that, the fisherman should decrease their effort to catch the squid. This is important in order to increase the number of squid and encourage the continuous harvesting of the species.